Pharmacokinetics of tralokinumab in adolescents with asthma: implications for future dosing. (1st October 2015) - Baverel, Paul G.; Jain, Meena; Stelmach, Iwona; She, Dewei; Agoram, Balaji; Sandbach, Sara; Piper, Edward; Kuna, Piotr
Abstract : Aims: Tralokinumab, an investigational human immunoglobulin G4 monoclonal antibody, potently and specifically neutralizes interleukin‐13, a central mediator of asthma. Tralokinumab has shown improvements in clinical endpoints in adults with uncontrolled asthma. The present study explored the pharmacokinetics (PK) and safety of a single tralokinumab dose, and utilized a population PK modelling and simulation approach to evaluate the optimal dosing strategy for adolescents. Methods: Adolescent subjects with asthma, using daily controller medication, received a single subcutaneous dose of tralokinumab 300 mg. Safety, immunogenicity and PK data were collected during a 57‐day follow‐up. A population PK model was developed using data from the present study and prior studies in adults. Simulations were performed to evaluate dose adjustment requirements for adolescents. Results: Twenty adolescents (12–17 years) were enrolled; all completed the study. No clinically relevant safety findings or antidrug antibodies were detected. PK parameters were similar to those observed in adults. PK modelling showed that body weight was a minor predictor of tralokinumab PK; after incorporating body weight into the PK model, a 15% (nonparametric 95% confidence interval 5%, 26%) lower clearance was found in adolescents compared with adults [173 (151, 209) vs . 204 (191, 229) ml day –1 ]. Simulations showed no therapeutically relevant differences in exposures between adolescent and adult populations, and similar PK profiles for weight‐based (4 mg kg –1 ) and fixed (300 mg) fortnightly subcutaneous doses of tralokinumab. Conclusion: Single‐dose administration of tralokinumab 300 mg in adolescents was well tolerated, with a PK profile similar to that in adults. Exposure predictions suggest that dose adjustment is not required for adolescents.